Experiments on energy, the environment, and sustainability - Isaac, R. Mark 1954-; Norton, Douglas A., 1984- (Research in experimental economics ;, 2011)
This volume will present experimental economics research focusing on issues of environmental quality and sustainability. Specific topics will include institutions for cap-and-trade, eco-tourism, urban sprawl, and optimal pollution control strategies. In addition to the traditional 'introduction', we are asking an expert on engineering issues in energy, the environment, and sustainability to write an essay highlighting the benefits to scientists and engineers of understanding human behaviour.